USING DNA BARCODE TO IMPROVE THE IDENTIFICATION OF MARINE FISH LARVAE, CASE STUDY COASTAL WATER NEAR JAKARTA AND BANDA SEA, INDONESIA - Arif Wibowo; Anthony Sisco Panggabean; Achmad Zamroni; Asep Priatna; Helman Nur Yusuf (Indonesian Fisheries Research Journal, 2018)
The sustainability of the exploitation of the Indonesian fishes depends heavily on many of fish’s basic information including both larvae distribution and dispersal. However, the identification of fish larvae and juvenile to species is very limited. In this study, we employed DNA barcoding techniques to identify marine fish larvae to a species level in Jakarta Bay and Banda Sea by comparing the querries with sequences from adult stage as reference library to contribute on biodiversity information on that particular area. The result revealed that in Jakarta Bay, the molecular marker of a 471 bp region of the mitchondrial cyctochrome c oxidase I gene (COI) has been successfully found to be species-specific, genetic distance within species (0.0 - 1.30 percent). There are total of 8 families, 5 genera and 5 species from a total 15 successful PCR that could be used to calculate the accuracy of larval fish identification in three taxonomic categories. Meanwhile in Banda Sea, for the adult specimens, after some of PCR experiment, we have successfully amplified 27 individuals, only 8 sequences available. There are a total 326 eggs and larvae which been collected from 19 stations, of the 28 successfully amplified PCR samples, 11 sequences were available for DNA analysis and at least 10 species used Banda Sea and surrounding area as their spawning ground. We prove the ability of COI barcodes to identify species level resolution from query sequences and to classify species from distinct geographical origins and determine of how the data retrieved give important information for proposing plans for conserving and managing of fisheries in the sea waters.